Strategies of Adaptation in the Finnish Publications of Marvel's Superhero Comics - Antola Laura (Wiley, 2022)
Superhero comics are an iconic product of American popular culture. Since the 1980s characters such as Spider-Man have become increasingly global, which raises questions about the way other cultures have appropriated the characters and made them their own. This article investigates the strategies of adaptation of Marvel’s superhero comic books into the Finnish media culture in the 1980s and 1990s. The article proposes that the concept of adaptation offers an understanding of transnational comics publishing that is new to the study of comics translations. Three strategies of adaptation were found: selection, cutting and pasting and domestication of the translation.